Aplicação da astronomia ao ensino de física e biologia - Santos, Iranéia Campos dos (2017)
Recognizing the importance of the insertion of Astronomy in our daily life, this dissertation has as main characteristic, to promote a holistic and interdisciplinary learning to the contents of Physics and Biology in classes of 1st and 2nd year of the High School of the Luís Eduardo Magalhães Model School in Feira de Santana. The problems related to the problems and difficulties in teaching science in high school are noted through reports cited in IDEB and PISA Research Against the background of the recommendations of the PCN +, supported by a STEM approach, support the proposal of this work, aimed at the development of activities promoting Science Teaching, anchored in technological and astronomical themes. Concerned with the legitimacy of distinguishing skills through the students' cognitive levels, the Marzano and SOLO Taxonomies were used for a hierarchical organization of cognitively organized learning objectives Following a contextualization of this theme, the activities were organized in structured tests of interest in the Research (ROSE); research and in-house study on relevant scientific topics in Astronomy and its related fields; survey of interdisciplinary issues related to Astronomy and Natural Sciences and their Technologies; development of support material structured in the form of Didactic Sequences; development of the Ares Project and culminating in the holding of the Science Fair; and creation of the interactive page on Facebook to publicize events and activities. As a result of more than two years of project development, statistical analyzes were performed for the validation of quantitative results, while a qualitative analysis is used for evaluations of cognitive taxonomic development. Both evaluations significantly showed that the project interventions produced a qualitatively and quantitatively relevant transformation in the learning and cognitive understanding process of the students, showing the relevance of the incorporation of contextualized S & T topics as motivating elements in the learning process